Synthesis and properties of lead iron niobate (PFN) - Youmee P. (2014)
Lead iron niobate, Pb(Fe1/2Nb1/2)O3 or PFN has been widely used as one of the constituents in multilayer capacitors, as it shows high dielectric constant (> 104) even with a sintering temperature of 1000°C. In this study, the oxalate route has been used for the synthesis of PFN powders. The formation of PFN phases in the calcined powders has been investigated as a function of temperature and dwell time by using X-ray diffraction (XRD) and Thermogravimetric and Differential Analyses (TG/DTA). It has been found that 100% perovskite phase of PFN was successfully obtained at a calcination temperature of 800°C for 3 h. The morphology of PFN was investigated by Scanning Electron Microscopy (SEM). PFN powders from the partial oxalate and the oxalate processes were pressed and sintered to obtain dense ceramics. Using XRD and SEM, the effects of sintering temperature on the phase assemblage and ceramic microstructure of PFN have been investigated. Dielectric properties of PFN ceramics have been studied using dielectric measurement. The dielectric constant of PFN ceramics synthesized by the partial oxalate process was much higher in comparison to that of PFN ceramics synthesized by the oxalate process at the same sintering temperature.